Italy : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper uses the tax-benefit microsimulation model for the European Union (EUROMOD) to evaluate possible reforms to modernize Italy's social safety net as well as ways to lower the tax wedge on labor. With a social safety net centered on pensions and the elderly and an array of income support schemes as well as a heavy tax burden falling on labor income, there is significant scope to improve Italy's system of taxes and transfers to promote growth and inclusion. The paper also simulates the cost of a modern safety net using EUROMOD. The paper also provides an overview of Italy's personal income tax regime, simulates the cost of moving toward a flatter regime that has previously been proposed by the government coalition and discusses some key reform principles. It is concluded that Italy needs a modern social safety net and a lower tax wedge on labor as part of a growth-friendly and inclusive fiscal consolidation package.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet